PENGALAMAN GURU SD DALAM MENGGUNAKAN SMART BOARD SEBAGAI STRATEGI PENGELOLAAN FOKUS BELAJAR MATEMATIKA - Khoirudin, Asmi; Handayani , Sri; Wasliman, Eva Dianawati (Universitas Islam Nusantara, 2026)
Maintaining students learning focus in mathematics presents a critical pedagogical challenge in the digital era, particularly as screen time increases and attention spans decline. This study explores elementary school teachers' experiences in utilizing Smart Board as a strategic tool for managing students' learning focus in mathematics instruction. Employing a qualitative phenomenological approach, in-depth interviews and non-participatory observations were conducted with upper-grade teachers (grades IV and V) at SDN 227 Margahayu Utara who had utilized Smart Board for a minimum of one semester. Data were analyzed using the Miles, Huberman, and Saldaña interactive model with triangulation and member checking for validity. Findings reveal that teachers develop six sophisticated pedagogical strategies: visual-interactive engagement, progressive participation, multimodal variability, content selectivity, rule-based interactivity, and technical anticipation. Teachers integrate dynamic visualization and real-time manipulation of mathematical objects to create anticipatory attention, with optimal session duration of 15-40 minutes to prevent attention fatigue. From an administrative perspective, successful implementation critically depends on comprehensive school support systems, including continuous professional development and responsive technical support. This study confirms that Smart Board effectiveness depends on teachers' pedagogical expertise rather than technological capabilities alone, requiring collaborative commitment between teachers and school administrators for systemic change